Immobilization of Xylanase Xyn II-ST4 and -ST5 with Biotinylated Poly(lactic-co-glycolic Acid) Nanosphere Carrier Increased Their Thermal and pH Stabilities - Gao1, Q.Y.; Xu2, G.C.; Chen1, H.L.; Zhou1, C.Y.; Zhang1, W.B. (Asian Journal of Chemistry, 2014)
Xyn II-ST4 and -ST5 are recombinant enzymes derived from Xyn II, a xylanase from Aspergillus niger prepared by replacing the serine and/or the threonine with arginine at its serine/threonine surface residues. Xyn II-ST4 and -ST5 were immobilized with poly(lactic-co-glycolic acid) based nanosphere carrier and crosslinked by glutaraldehyde to improve their thermal and pH stabilities. Single factor analyses, orthogonal experiments and variance analyses were conducted to determine the significant factors for immobilization. Results showed that the recovery of enzymatic activities of immobilized Xyn II-ST4 and -ST5 were 79.68 and 81.23 %, respectively. In addition, the optimum temperature for ST4 and ST5 was increased by 5 and 3 °C, respectively and the optimum pH varied from 4.5 to 5. Results suggested that the poly(lactic-co-glycolic acid) nanosphere is a potential carrier for the immobilization of Xyn II-ST4 and -ST5 because the poly(lactic-co-glycolic acid) nanosphere can improve their thermal and pH stabilities.